Implementation of Character Education Based on Tahfidzul Qur'an at the Yanbu'ul Qur'an Tahfidz Islamic Boarding School in Menawan Village - Farohi, Ahmad; Fatmawati, Noor; Maula, Nurkholifatul (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
This study explores the integration of Tahfidzul Qur'an with character education at the Yanbu'ul Qur'an Tahfidz Islamic Boarding School in Menawan Village. Utilizing a library research method, the study examines how Quran memorization (Tahfidzul Qur'an) is systematically embedded into the educational framework to foster noble character traits among students, such as discipline, politeness, solidarity, religious character, and patriotism. The analysis highlights the interactions and activities within halaqah sessions, identifying them as critical moments for character development. Furthermore, this research addresses a gap in the existing literature by investigating the specific role of Quran memorization in character formation, a topic that has been insufficiently explored in previous studies. The findings indicate that the structured memorization of the Qur'an, alongside targeted character education strategies, significantly contributes to the holistic development of students, offering a robust model for character education in similar Islamic educational institutions.